2013
DOI: 10.1073/pnas.1306779110
|View full text |Cite
|
Sign up to set email alerts
|

Illusory ownership of a virtual child body causes overestimation of object sizes and implicit attitude changes

Abstract: An illusory sensation of ownership over a surrogate limb or whole body can be induced through specific forms of multisensory stimulation, such as synchronous visuotactile tapping on the hidden real and visible rubber hand in the rubber hand illusion. Such methods have been used to induce ownership over a manikin and a virtual body that substitute the real body, as seen from firstperson perspective, through a head-mounted display. However, the perceptual and behavioral consequences of such transformed body owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
508
6
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 544 publications
(557 citation statements)
references
References 41 publications
40
508
6
3
Order By: Relevance
“…These findings are fundamentally important, as they suggest a link between the ongoing perceptual experiences of the body and the world from the first-person perspective and the hippocampal episodic memory system. This empirical observation provides a basis for models of episodic memory (1, 2, 7, 8, 29, 31, 32, 34) and self-consciousness (10,13,14,37), and it is a striking example of embodied cognition (38,39), in which multisensory body self-perception directly influences a specific higher cognitive function, namely the episodic long-term memory system. Under normal conditions, an individual experiences the world from the perspective of the physical body, and his/her center of The activation of the previously well-established network of episodic retrieval of life events when contrasting the retrieval conditions with the baseline imagery condition (main effect of retrieval) (all activations show P < 0.05, corrected; the scale denotes t values; the activations were superimposed on a mean T1-weighted structural scan in the MNI standard space generated from the structural scans of all participants, and masked with the search space of the episodic autobiographical network).…”
Section: Discussionmentioning
confidence: 91%
“…These findings are fundamentally important, as they suggest a link between the ongoing perceptual experiences of the body and the world from the first-person perspective and the hippocampal episodic memory system. This empirical observation provides a basis for models of episodic memory (1, 2, 7, 8, 29, 31, 32, 34) and self-consciousness (10,13,14,37), and it is a striking example of embodied cognition (38,39), in which multisensory body self-perception directly influences a specific higher cognitive function, namely the episodic long-term memory system. Under normal conditions, an individual experiences the world from the perspective of the physical body, and his/her center of The activation of the previously well-established network of episodic retrieval of life events when contrasting the retrieval conditions with the baseline imagery condition (main effect of retrieval) (all activations show P < 0.05, corrected; the scale denotes t values; the activations were superimposed on a mean T1-weighted structural scan in the MNI standard space generated from the structural scans of all participants, and masked with the search space of the episodic autobiographical network).…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, two of these studies Maister et al, 2013) found that the amount that participant's racial bias decreased was correlated with the strength of the ownership they felt for the hand, suggesting that this effect is partly caused by the increased overlap between the self and the racial out-group. Effects of embodiment on racial bias have also been found when using VR to generate a full-body illusion (Peck, Seinfeld, Aglioti, & Slater, 2013) and similar changes in implicit attitudes to children have been found after embodying a child avatar (Banakou, Groten, & Slater, 2013). However, another recent study (Estudillo & Bindemann, 2016) found no evidence that multisensory stimulation of the face led to changes in racial bias.…”
Section: Embodimentmentioning
confidence: 82%
“…Based on past results we expected that the sync condition would result in a substantially greater illusion of body ownership over the VB than the async condition (11,13,(21)(22)(23). The vibrations factor was designed to enhance the sense of speaking by applying vibratory feedback on the thyroid cartilage to coincide with the period that the embodied avatar was speaking (Von) or no vibratory feedback (Voff).…”
Section: Significancementioning
confidence: 99%
“…When average-sized adults have an illusion of body ownership over smaller or larger bodies, this results in changes in the perception of object sizes (12). Even more remarkably, the illusion of body ownership of adults over a virtual child body leads to overestimation of object sizes and changes in implicit attitudes about the self substantially beyond changes induced by the illusion of ownership of an adult shaped body of the same size as the child (13). Hence the type of body appears to carry with it physiological, perceptual, and even deepseated attitudinal correlates.…”
mentioning
confidence: 99%